Efficacy of Exercise on Breast Cancer Outcomes: A Systematic Review and Meta-analysis of Preclinical Data - Figueira, Ana Cristina Corrêa; Cortinhas, António; Soares, Jorge Pinto; Leitão, José Carlos; Ferreira, Rita Pinho; Duarte, Jose Alberto (International Journal of Sports Medicine, 2018)
The use of preclinical models to investigate antitumor effects of exercise on breast tumor (BT) development and progression are critical. However, published results have not been quantitatively summarized or examined for potential exercise-moderating variables. We conducted this review to summarize and quantify the effect-size of exercise on BT outcomes in preclinical studies. A literature search was performed in MEDLINE, PubMed, Web of Science and System for Information on Grey Literature in Europe (SIGLE) databases. Risk of bias was assessed using SYRCLE’s RoB tool. A total of 116 correlations were performed to analyze 28 preclinical studies published through December 2016, which included 2,085 animals and 51 exercise programs. Positive effects of small, medium and large magnitude were observed in tumor incidence, growth and multiplicity, respectively. In the tumor microenvironment, positive effects of large magnitude were also observed in proliferation and apoptosis but not in angiogenesis. Moderator variables correlated with higher intervention effects were identified along with a considerable heterogeneity in exercise protocols that precluded us from clearly perceiving the benefits of exercise exposure. In conclusion, exercise performed under specific conditions benefits BT outcomes. Preclinical studies with exercise designs mimicking exercise exposure that can be used in clinical contexts are needed.
Keywords: tumor burden; tumor microenvironment; proliferation; apoptosis; angiogenesis; effect size